Modeling seasonal trends in optimum temperatures over India - Nishtha Agrawal (IWA Publishing, 2021)
Global warming and changes in seasonal temperature can severely affect the general circulation and precipitation distribution of a region. Therefore, it becomes essential to analyze seasonal trends in air temperature with changing climate. The present study evaluates the troposphere temperature extremes over India during different seasons. We intend to identify significant trends in temperature distribution in different regions of India using the Mann–Kendall test. Further, we have calculated indices concerning temperature extremes to make inferences about the nature of this monotonicity at four pressure levels on a seasonal and annual basis. The temperature data being used in our analysis is obtained from the output of a Regional Climate Model version 4.6 (RegCM v4.6). The monthly temperature values are taken for 25 years (1982–2006) from the model output. We observed that the model captured temperature climatology is coherent with our theoretical analysis. Results of our study reveal a significant (p < 0.05) trend in TT during all the seasons in major parts of the country in the lower troposphere. The upper troposphere, on the other hand, does not show any significant trend during most of the seasons. The identification of these changes can be useful for analysis of coastal vulnerability and extreme weather conditions. HIGHLIGHTS Changes in seasonal temperature can severely affect general circulation and precipitation distribution of a region; therefore, it is essential to analyze seasonal trends in air temperature with changing climate.; We evaluate the troposphere temperature extremes over India during different seasons and trends in temperature distribution in different regions of India. Indices concerning temperature extremes to make inferences about the nature of this monotonicity at four pressure levels on a seasonal and annual basis are also calculated.; The monthly temperature values are taken for 25 years (1982–2006) from the model output of RegCM v4.6.; We observed a significant trend in TT during all the seasons in major parts of the country only in the lower troposphere and no such trend was observed in the upper troposphere during most of the seasons.; Findings can be useful in examining the perturbed state of the atmosphere, shifts in weather patterns and its impact on mean seasonal circulation in the near future.;